WEIGHT GAIN AND HEALTH CONDITION OF PREGNANT MACACA FASCICULARIS AT PT BIO FARMA (PERSERO) - Mieska Despitasari (Pusbindiklat - LIPI, 2012)
produced vaccines. This research aims to study the increase in body weight and health condition of M. fascicularisin PT Bio Farma’s captivity. Nine M. fascicularis were grouped into three treatments of feeding trials with differentprotein levels. Data were analyzed by Analysis of Variance. Highest protein level showed the highest proteinintake (16,28±0,62%) with highest feeding efficiency (94,72±3,60%). It gave effect on the high total weight gain.M. fascicularis’ health condition was measured by total plasma protein and hemoglobin levels. The highest totalprotein plasma level has been performed by the objects who take the highest protein level. Results showed thatmonkeys’ hemoglobin levels were decreased – except monkeys that take 12,91% protein level – this is the indicationof nutritional anemia during pregnancy.